2023
DOI: 10.1093/geroni/igad071
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone Increases the Risk of Hypertension in Older Chinese Adults: A Population-Based Longitudinal Study

Abstract: Background and Objectives Cross-sectional studies have suggested a potential association between living alone and hypertension risk, but longitudinal evidence remains limited. We aimed to investigate the correlation between living alone, alterations in living arrangements, and hypertension risk among older adults utilizing a population-based longitudinal design. Research Design and Methods The study included 8,782 older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Their psychological well-being is associated with increased income and internet use. This may be because older adults with higher economic status can fulfill basic needs for food, shelter, and clothing, then pursue higher-level needs of healthy social and recreational activities to safeguard mental health, effectively alleviating feelings of helplessness and loneliness from loss of a spouse or children leaving home, and elevating positive emotions ( 7 , 34 ). Additionally, greater income implies solitary older adults can access and utilize more medical resources, reducing mental health risks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their psychological well-being is associated with increased income and internet use. This may be because older adults with higher economic status can fulfill basic needs for food, shelter, and clothing, then pursue higher-level needs of healthy social and recreational activities to safeguard mental health, effectively alleviating feelings of helplessness and loneliness from loss of a spouse or children leaving home, and elevating positive emotions ( 7 , 34 ). Additionally, greater income implies solitary older adults can access and utilize more medical resources, reducing mental health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Older individuals living alone, separated from their children or other family members, confront numerous challenges, including inconveniences, difficulties, and safety hazards in home-based care ( 6 , 7 ). A cohort study showed that living alone increases the risk of hypertension in older adults in China ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations